PERAN ORGANISASI E-SPORTS DALAM AKSESIBILITAS UNTUK PEMAIN DISABILITAS - Fakhriy Dinansyah; Charlie Tjokrodinata; Cendera Rizky Anugerah Bangun (Ultimacomm: Jurnal Ilmu Komunikasi, 2022)
The Indonesian e-sports industry cannot be separated from the role of organizations that oversee and manage all activities of e-sports players, which are expected to provide better accessibility for people with disabilities to be equal in recording achievements in the field of e-sports. This problem is closely related to the increase in internet access and the use of smartphones which are commonly used by people with disabilities, including playing games. This study aims to determine whether e-sports organizations as stakeholders provide accessibility for persons with disabilities. This study uses previous research that analyzed persons with disabilities in various roles in the new media ecosystem. Also, the fact that accessibility refers to the ability of a person with one or more disabilities to make meaningful use of media technology. Standpoint theory is the main theory as the basis and tool for analyzing the results of this study. This research uses a qualitative case study method with data collection techniques through interviews and literature studies and a post-positivist research paradigm. This study indicates that Esports Organizations in Indonesia have not been able to play a role in providing accessibility for gamers with disabilities. Of the three formal organizations, only IESPA has special attention by creating a para-Esports division for people with disabilities. Meanwhile, AVGI & PB ESI do not yet have a specific program. On the other hand, community-based informal organizations such as EAI have a great interest in being able to advocate for gamers with disabilities. Keywords: disability, accessibility, e-sports, new media, organization